International Conference on Horizontal Well Technology 1996
DOI: 10.2118/37056-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Analysis of Axial Force Along Coiled Tubing in Inclined/Horizontal Wellbores

Abstract: Thm paper was prepared for presentabon at the 19S6 SPE Intemabonal ConfereM on Hcmzontat Well Technology held m Calgary, Canada, 18-20 Novem* 19% This papr was selected for presentawan by an SPE Prqrem Committee follovmg rewew of Inlormabcm cmtamed m an abstraci Submitted by the author(s) Contents of thm papw, as presented, have not been rewewed by ths %clely of Petroleum Engineers and are subject to wrractmn by the author(s) Th!s material, as presented, does not necessarily reflect any pmbon of Ihe Scuety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…To simplify Paslay's derivation, a sine function buckling shape is assumed and then Eq. (13) can be directly deduced with the energy method (Chen et al 1990;Miska et al 1996;Liu 1999), Gao et al (1998) obtained an identical solution with stability analyses on the approximate linear form of the buckling equation. The theoretical results are close to the Dellinger's experiments (Dellinger et al 1983), and the fitting formulas for horizontal wellbores from the experimental data are F crs ¼ 2:93EI 0:479 q 0:522 r À0:436 .…”
Section: Straight Inclined and Horizontal Wellboresmentioning
confidence: 98%
See 2 more Smart Citations
“…To simplify Paslay's derivation, a sine function buckling shape is assumed and then Eq. (13) can be directly deduced with the energy method (Chen et al 1990;Miska et al 1996;Liu 1999), Gao et al (1998) obtained an identical solution with stability analyses on the approximate linear form of the buckling equation. The theoretical results are close to the Dellinger's experiments (Dellinger et al 1983), and the fitting formulas for horizontal wellbores from the experimental data are F crs ¼ 2:93EI 0:479 q 0:522 r À0:436 .…”
Section: Straight Inclined and Horizontal Wellboresmentioning
confidence: 98%
“…According to Wu, the critical helical buckling load is 2 ffiffi ffi 2 p À 1 times the critical sinusoidal buckling load. Miska et al (1996) assumed that the axial force increased linearly in the entire loading process and found that the critical helical buckling load was 2 ffiffi ffi 2 p times the critical sinusoidal buckling load. Miska et al (1996) also proved that the sinusoidal buckling configuration became unstable (b ¼ 1:875) before the tubular string changes to the helical buckling configuration.…”
Section: Straight Inclined and Horizontal Wellboresmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate the method a MATLAB program was elaborate and the following example was analyzed, [6,7,13] Figure 3 shows the dependence angle θ versus axial force, dependence found by the computer code. The Euler buckling force is 7.45 N (see figure 3a) and much higher force values were studied.…”
Section: Numerical Examplementioning
confidence: 99%
“…The problem is highly complicated because it involves a geometrical non-linearity to which the friction has to be added. Several theoretical models were proposed, all of them based on analytical models, some of them complicated, [1,2], or based on simplified (or even very simple) models using in general a variational approach, [3][4][5][6][7][8][9][10][11][12]. Experimental measurements were performed as well: some works are based only on experiments, [13,14], while in other works the experiments were meant to verify the theoretical models, [1,2,4,11,12].…”
Section: Introductionmentioning
confidence: 99%